Making the Most of Public Investment in MENA and CCA Oil-Exporting Countries - Albino, Maria (Staff Discussion Notes; Staff Discussion Notes ;, 2014)
Over the past decade, rising oil prices have translated into high levels of public investment in most MENA and CCA oil exporters. This has prompted questions about the efficiency of public investment in generating growth and closing infrastructure gaps, as well as concerns about fiscal vulnerabilities. When public investment is inefficient, higher levels of spending may simply lead to larger budget deficits, without sufficiency increasing the quantity or quality of public infrastructure in support of economic growth. This paper examines the efficiency of public investment in the MENA and CCA oil exporters using several techniques, including a novel application of the efficiency frontier analysis, estimates of unit investment costs, and assessments of public investment processes. The analysis confirms that these oil exporters have substantial room to improve public investment efficiency. Reforms in the public financial and investment management systems are needed to achieve this objective.